Growers` Attitudes towards growing and marketing Papyrus plant in Al-Qaramous Village, Sharqia Governorate - Fahmy, Maha Mohamed; Faied, Engy Khairy; Elkholy, Amany Said (Journal of agricultural, environmental and veterinary sciences, 2022)
This research attempts for identifying the Growers` Attitudes towards growing and marketing Papyrus plant, identifying the significant relationships between Socio- economic variables and the growers' Attitudes towards growing and marketing Papyrus, in addition, describing the present situation of growing and marketing Papyrus plant. Identifying the respondents' opinions on the problems which facing growing and marketing Papyrus and there suggestions to solve them.Methodology: This study was conducted on a random sample of 88 growers in Al-Qaramous Village, Abu kabir District, Sharqia Governorate, Egypt; data were collected using a pretested questionnaire via a personal interview during August 2022. Data were analyzed using qualitative and quantitative statistical tools: correlation coefficient, frequencies and percentages.Results: The main findings revealed that the majority of respondents had a moderate degree of attitude towards growing and marketing Papyrus. A significant positive relationship was also revealed between the growers’ attitudes towards growing and marketing Papyrus and the following independent variables: farm tenure size, the area of land cultivated with other crops and age. The most important problems observed by the research in the field of cultivation and marketing of the Papyrus are: the need of the Papyrus for large quantities of water with its unavailability and irregularity, the lack of fertilizer in the agricultural associations, and the plant's need for large quantities of fertilizers.Recommendations: According to the results, the research presents the following recommendations: Increasing grower’ awareness of the importance of papyrus cultivation by implementing training programs in this regard, and providing technical cadres from agricultural extension agents and specialists in the field of Papyrus cultivation, the necessity of providing the prescribed quotas of fertilizers for the cultivation of this plant, and increasing them in line with the fertilizer needs of the crop and finally the need for opening different markets to market the Papyrus crop to suit its different uses.
Keywords: Growers` Attitudes; growing; marketing; Development; Papyrus